Chediak Higashi Syndrome masquerading as acute leukemia / storage disorder - A rare case report - Baig, Mirza Asif; Sirasgi, Anil (International Journal of Research in Medical Sciences, 2017)
Chediak higashi Syndrome (CHS) is a rare autosomal recessive multisystem disorder with a defect in granule morphogenesis with giant lysosomes in leucocyte and other cells. CHS is a rare disease, approximately 200 cases have been reported so far. It was described in detail by Chediak in 1952 and Higashi in 1954. 1½ year old male child presented with multiple hypopigment patches on lower extremities, light colored hair, Hepatosplenomegaly and generalised Lymphadenopathy. PBS shows giant prominent liliac to purple granules in neutrophils, band forms, few lymphocytes and monocytes. Bone marrow is hypercellular showing giant prominent gray blue to purple heterogeneous granules often multiple seen in many myeloid precursors, Neutrophils, few lymphocytes and monocytes. Occasional lymphocytes shows single giant liliac inclusions. Erythropoiesis, myeloid series and Megakaryocytes are mildly increased. Hemophagocytosis noted. CHS is characterised by partial oculocutaneous albinism, frequent fatal bacterial infections, bleeding diathesis and peripheral + Cranial nerve palsies. This disorder further culminates into accelerated phase (Lymphoproliferative Syndrome) progressing into pancytopenia. CHS is due to single gene mutation in LYST (CHS) gene localized to 1q chromosome. The diagnostic hallmark of CHS is presence of giant purple to blue violet inclusions in leucocytes. In this study granules are more prominent in Bone marrow than in PBS correlating well with previous studies. Approximately 85% of the cases, of CHS culminates into Accelerated phase showing Lymphohistiocytic infiltration progressing to pancytopenia and death due to infection. The very rare nature of this disease and its grave prognosis merits its reporting.